2016
DOI: 10.1186/s12884-016-0900-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for small-for-gestational-age and preterm births among 19,269 Tanzanian newborns

Abstract: BackgroundFew studies have differentiated risk factors for term-small for gestational age (SGA), preterm-appropriate for gestational age (AGA), and preterm-SGA, despite evidence of varying risk of child mortality and poor developmental outcomes.MethodsWe analyzed birth outcome data from singleton infants, who were enrolled in a large randomized, double-blind, placebo-controlled trial of neonatal vitamin A supplementation conducted in Tanzania. SGA was defined as birth weight <10th percentile for gestation age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
6
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 24 publications
8
62
6
2
Order By: Relevance
“…The risk of preterm births was higher among both mothers younger than 20 years and above 35 years. Several other studies have also reported linking both younger and older maternal age with preterm births [4,[21][22][23][24][25]. The risk of preterm births was also higher among mothers with education lower than secondary level had a higher risk of having preterm births.…”
Section: Discussionmentioning
confidence: 90%
“…The risk of preterm births was higher among both mothers younger than 20 years and above 35 years. Several other studies have also reported linking both younger and older maternal age with preterm births [4,[21][22][23][24][25]. The risk of preterm births was also higher among mothers with education lower than secondary level had a higher risk of having preterm births.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, infant weight at four days post-delivery was comparable between young and AMA mothers. In humans, one driver of the small gestational phenotype is pre-term delivery 7578 . This may be a possible explanation for why we did not observe low birth weights in vervets, since AMA did not elicit pre-term delivery in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Given their association with preterm birth, authors may report effect estimates of these confounders alongside the effect estimate for preeclampsia, 13,18 and even more commonly when evaluating preeclampsia as one of multiple risk factors for preterm birth. 17,23,[26][27][28][29] Here, we provide a didactic example of an analysis to estimate the hypothesised effect of preeclampsia on preterm birth among singletons ( Figure 2). In Model 1, we estimate the risk ratio for preeclampsia, adjusting for previous preterm birth, alcohol abuse, and maternal education as secondary factors.…”
Section: Motivating Examplementioning
confidence: 99%
“…Because these and other risk factors for preeclampsia are also associated with preterm birth, their potential for confounding the effects of preeclampsia on preterm birth must be considered. Given their association with preterm birth, authors may report effect estimates of these confounders alongside the effect estimate for preeclampsia, and even more commonly when evaluating preeclampsia as one of multiple risk factors for preterm birth …”
Section: Introductionmentioning
confidence: 99%